Structure-based drug designing against Leishmania donovani using docking and molecular dynamics simulation studies: exploring glutathione synthetase as a drug target - Sarma M.; Borkotoky S.; Dubey V.K. (My University, 2025)
In the pursuit of developing novel anti-leishmanial agents, we conducted an extensive computational study to screen inhibitors from the FDA-approved ZINC database against Leishmania donovani glutathione synthetase. The three-dimensional structure of Leishmania donovani glutathione synthetase was constructed by homology modeling, using the crystallographic structure of Trypanosoma brucei glutathione synthetase as a template. Subsequently, molecular docking studies were carried out for a large number of compounds using AutoDock Vina. Among the screened compounds, we selected the top five with strong binding affinity to Leishmania donovani glutathione synthetase but having a very low affinity to its human homolog. Further investigations on protein-ligand complexes were done by conducting molecular dynamics (MD) simulation and MM/PBSA analysis. The results revealed that Olysio (Simeprevir) exhibited the lowest binding energy (-89.21 kcal/mol), followed by Telithromycin (-45.34 kcal/mol). These findings showed that these compounds have the potential to act as inhibitors of glutathione synthetase. Hence, our study provides valuable insights for the development of a novel therapeutic strategy against Leishmania donovani by targeting the glutathione synthetase enzyme. Communicated by Ramaswamy H. Sarma. © 2023 Informa UK Limited, trading as Taylor & Francis Group.